2014
DOI: 10.1130/b30836.1
|View full text |Cite
|
Sign up to set email alerts
|

Coastal response to late-stage transgression and sea-level highstand

Abstract: Coastal morphologic features associated with past shoreline transgressions and sealevel highstands can provide insight into the rates and processes associated with coastal response to the modern global rise in sea level. Along the eastern and southern Brazilian coasts of South America, 6000 years of sea-level fall have preserved late-stage transgressive and sea-level highstand features 1-4 m above present mean sea level and several kilome ters landward of modern shorelines. GPS with real-time kinematics data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…However, this change in shoreline trend and initiation of barrier progradation clearly occurred when RSL rise slowed to 1.3 mm/yr. This rate is in line with that reported by Hein et al (2014b), who investigated coastal response to RSL for Holocene highstand barrier systems in Brazil and found that, despite great regional and local variability, stabilization of the transgressive barriers occurred when RSL rise decelerated to < 2 mm/yr, while higher rates led to retrogradational barriers. Moreover, the rate of RSL rise at Saint-Pierre-etMiquelon over the period of barrier formation is similar to rates reported during the period for development of similar systems (barriers or beach ridge plains) in the northwest Atlantic.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…However, this change in shoreline trend and initiation of barrier progradation clearly occurred when RSL rise slowed to 1.3 mm/yr. This rate is in line with that reported by Hein et al (2014b), who investigated coastal response to RSL for Holocene highstand barrier systems in Brazil and found that, despite great regional and local variability, stabilization of the transgressive barriers occurred when RSL rise decelerated to < 2 mm/yr, while higher rates led to retrogradational barriers. Moreover, the rate of RSL rise at Saint-Pierre-etMiquelon over the period of barrier formation is similar to rates reported during the period for development of similar systems (barriers or beach ridge plains) in the northwest Atlantic.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…Differences in prevailing wind directions, sediment supply, or the sizes of bays and catchments may have contributed to differences in the evolution of these transgressive coastal systems. However, several studies performed on barrier island and non‐rocky coastal plain systems have concluded that bedrock topography plays the most significant role (Buynevich & Fitzgerald, ; Locker et al ., ; Tessier et al ., ; Cooper et al ., ; Traini et al ., ; Hein et al ., ). All of the studied systems herein have significant differences in the elevations of the pre‐Holocene bedrock over which the coastal sediments accumulated, which led to differences in the timing of flooding during the Holocene.…”
Section: Discussionmentioning
confidence: 97%
“…Niedoroda et al, 1985;Boyd et al, 1992;Roy et al, 1994;Carrasco et al, 2016). Models of post-glacial coastal systems incorporating data about the antecedent pre-Holocene topography of the bedrock and detailed Holocene stratigraphies are less common Hein et al, 2014;Fruergaard et al, 2015a,b). Among these, only a few have dealt with rocky coastal systems that included freshwater perched lakes separated from the open sea by extensive sand barriers (Devoy et al, 1996;Bao et al, 2007;Massey & Taylor, 2007;Cooper et al, 2012), but they did not investigate the parameters and mechanisms involved in their formation from a sequential stratigraphy perspective.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the eustatic sea-level rise following the last glacial maximum resulted in a highstand approximately 5.8 ka ago, encroaching in some locations upon Pleistocene highstand barriers (HORN FILHO et al, 1997;CARUSO JR et al, 2000, DOMINGUEZ, 2009). Since then the sea level has fallen 2 to 4 m (SUGUIU et al, 1985;LESSA, 1997;ANGULO et al, 2006;HESP et al, 2009;MCBRIDE et al, 2013;HEIN et al, 2013HEIN et al, , 2014 as a consequence of global isostasy, as demonstrated by MITROVICA and MILNE (2002).…”
Section: Study Areamentioning
confidence: 99%
“…This part of the coast is characterized by the high relief of the nearby Serra do Mar range, with a series of grabens and horsts parallel to the current coastline that were created by the Tertiary collapse (58 M yr BP) of a large Cretaceous plateau (ZALÁN; OLIVEIRA, 2005), giving rise, over the course of 30 million years, to Large-scale sea-level fluctuations throughout the Quaternary resulted in the deposition of a series of transgressive barriers and regressive barrier-strandplain systems, thus straightening the bedrock-dominated shoreline (DOMINGUEZ, 2009;KLEIN et al, 2010;MCBRIDE et al, 2013;HEIN et al 2013HEIN et al , 2014. Two Quaternary barriers, dating from the Oxygen Isotopic Stage (OIS) 5e and mid-Holocene highstands (SUGUIO et al, 1985;VILLWOCK et al, 1986;MARTINS et al, 1988) have been identified on the central coast of Santa Catarina where the Serra do Mar mountain range abuts the modern coast (HORN FILHO et al, 1997;CARUSO JR et al, 2000;MCBRIDE et al, 2013;HESP et al, 2009;HEIN et al, 2013HEIN et al, , 2014.…”
Section: Study Areamentioning
confidence: 99%